Interaksi interpersonal dan stres kerja dosen di STIKES X Bengkulu - Rina Aprianti; Agus Surono (Berita Kedokteran Masyarakat (BKM), 2017)
Interpersonal interaction and lecturer work stress in private universityPurposeThis paper discussed how and why the weakness of interpersonal interaction can lead to lecturer work stress.MethodThis analytic survey research was conducted with a cross-sectional approach involving 36 permanent lecturers of a private university. The independent variables were the working period and interpersonal interaction, the dependent variable was the work stress.ResultsThis paper found 50% of lecturers still lack interpersonal interaction. The problem was in communication among lecturers and university leaders, and awareness to build interpersonal interaction in the work environment. Lecturers with good interpersonal interactions have lower stress levels. Social support is very useful to strengthen the psychological aspects of lecturers in their activities.ConclusionThis paper concluded the relationship between interpersonal interaction with work stress. University need to regularly facilitate joint agenda for all staff to encourage close interpersonal interaction.